The interdependence of R&D activity and debt financing of young firms - Helmut Fryges; Karsten Kohn; Katrin Ullrich (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
We investigate the interdependence of debt financing and R&D activities of young firms. Using micro-level data of the KfW/ZEW Start-up Panel, our estimation results show that firm characteristics are more important than personal characteristics of the founders for explaining young firms' leverage, whereas firm characteristics and human capital of both founders and employees heavily influence R&D intensity. Applying a bivariate Tobit model, we find that there is a positive interdependent relationship between the share of loan financing and R&D intensity. A higher share of loan financing allows for more R&D in young firms and, at the same time, a higher R&D intensity allows for a higher loan share. This relationship cannot be detected by merely estimating single-equation models for R&D intensity and debt financing.
Keywords: G32; O32; L26; 330; innovation financing; capital structure; start-ups; KfW/ZEW Start-up Panel; Germany